Application of remote sensing data for environmental monitoring in semiarid mountain areas : a case study in Yemen Mountains - Almhab, Ayoub (2007)
Remote sensing has been proved to be a very useful technology in the investigation of surface parameters and environment monitoring when large areas is covered. In this paper, the complementarily between two optical remote sensing data Landsat TM and Radar Sat (OEM) were used to estimate and describes the affected surface temperature by elevation, slope and aspect of the land surface, in additional to effect of solar radiation on surface temperature and relation of elevation to wind speed. The two important factors related· temperature difference near surface (dT) function is the relationship between wind speed and the surface temperature, and the change of the temperature difference near surface dT function for each image was investigated. The information in this paper provides good background for Remote Sensing applications for monitoring the environment especially in the mountainous areas. An application for computing temperature map over Sana'a Basin in central mountainous in Yemen is presented.